The Fight against Technological Unemployment. Analysis of Subnational Cases in Mexico - Cabrero Mendoza, Enrique; Guajardo Mendoza, Miguel Adolfo (Revista del CLAD Reforma y Democracia, 2022)
This paper studies the risk of technological unemployment in Mexico, both at the national level and in two states: Querétaro (QRO) and San Luis Potosí (SLP). Using the methodology of Frey and Osborne (2013) adapted to the INEGI’s National Occupations System, it was found that both QRO (51%) and SLP (57%) are below the national average (67%) in terms of technological unemployment risk. However, the situation changes when analyzing some strategic sectors in QRO, such as food with an average unemployment rate of 84%, automotive with 75% and household appliances with 92%. The same occurs in SLP, where the food sector reaches 95% and the automotive sector 93%. Therefore, this phenomenon cannot be analyzed only from a national or state perspective, a sectoral look is also required. In addition, it was found that the probability of being at high risk is higher for women, younger age groups, and people with lower levels of education on average. Finally, it was identified that for all the sectors studied, the great mass of people at high risk is found in the middle schooling segments. This could be interpreted as an imminent polarization of employment, which would imply the concentration of the employed at the extremes, in terms of skills, with a gradual disappearance of the segments in the middle. The question remains open: What public policy agenda should Latin American countries deploy in this area?
Keywords: Employment Policy; Unemployment; Technological Change; Automation; National Problem; Local Problem; Federal Entities; Case Analysis; Mexico